Development of permeability test method for porous concrete block pavement materials considering clogging. (15th August 2016) - Lin, Wuguang; Park, Dae-Geun; Ryu, Sung Woo; Lee, Byeong-Tae; Cho, Yoon-Ho
Highlights: The causes of clogging were investigated and a clogging simulator was developed to evaluate the sustainable permeability of porous concrete block pavement. Furthermore, a test method for verifying the sustainability of infiltration which can predict and assess the permeability performance was proposed. It was found that the pores were easily clogged with the vibration frequency increased, but with the amount of contaminants increased to a degree clogging had less influence on vibration. Abstract: Pervious pavement has been used widely due to efficient hydrological characteristics such as reduction of runoff during floods, providing delay of rainwater into sewer systems and ground water quality improvement. However, clogging prevents it from functioning properly due to sedimentation after a short period of service, which results to poor permeability and performance of pervious pavement. In this study, the causes of clogging were investigated and a clogging simulator was developed in order to evaluate the sustainable permeability of porous concrete block pavement in advance. Furthermore, a test method for verifying the sustainability of infiltration which can predict and assess the permeability performance by years of service was proposed. In addition, the penetration of contaminants also varies depending on vehicle vibration and the rainwater that permeates together with it. It was found that the pores were easily clogged with the vibration frequency increased, but with the amount of contaminants increased to a degree clogging had less influence on vibration. When various types of porous concrete block pavers were evaluated with the proposed sustainable permeability test method, the coefficient of permeability before and after the test have shown very high correlation.